2021
DOI: 10.1088/1361-6560/ac16ec
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic pulmonary perfusion images from 4DCT for functional avoidance using deep learning

Abstract: Purpose. To develop and evaluate the performance of a deep learning model to generate synthetic pulmonary perfusion images from clinical 4DCT images for patients undergoing radiotherapy for lung cancer. Methods. A clinical data set of 58 pre- and post-radiotherapy 99mTc-labeled MAA-SPECT perfusion studies (32 patients) each with contemporaneous 4DCT studies was collected. Using the inhale and exhale phases of the 4DCT, a 3D-residual network was trained to create synthetic perfusion images utilizing the MAA-SPE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 45 publications
1
14
0
Order By: Relevance
“…Meanwhile, the results from this and our previous study were also consistent with the work of Porter et al. ( 19 ) on synthetic pulmonary perfusion images from 4D-CT, and a Spearman correlation of 0.7 between 4D-CT- and SPECT-based perfusion images was reported. In this study, to reduce the influence of image noise, all the ventilation images finally went through a smoothing with a 9 × 9 × 9 box median filter.…”
Section: Discussionsupporting
confidence: 93%
“…Meanwhile, the results from this and our previous study were also consistent with the work of Porter et al. ( 19 ) on synthetic pulmonary perfusion images from 4D-CT, and a Spearman correlation of 0.7 between 4D-CT- and SPECT-based perfusion images was reported. In this study, to reduce the influence of image noise, all the ventilation images finally went through a smoothing with a 9 × 9 × 9 box median filter.…”
Section: Discussionsupporting
confidence: 93%
“…An asymmetrical structural similarity index measure (aSSIM) was used as the secondary loss function for the generator, which was based on the work of Porter et al. who used an asymmetrical mean absolute error (AMAE) for predicting perfusion defects 29 . Gerard et al.…”
Section: Methodsmentioning
confidence: 99%
“…15 Currently, functional lung imaging and research are based on physical properties of the image such as calculating local CT density changes 16 or calculating regional volume changes using the Jacobian from deformable image registration (DIR). 17 Recently, there have been works published that use machine learning to predict radiation-induced pneumonitis, [18][19][20][21] derive ventilation [22][23][24][25][26] and perfusion maps [27][28][29][30] , and perform segmentation [31][32][33][34] and DIR. [35][36][37][38] However, no work to date has investigated using machine learning to model local pulmonary ventilation change following RT.…”
Section: Introductionmentioning
confidence: 99%
“…20 4DCT perfusion images have been synthesized using a deep learning approach with MAA-SPECT as the nuclear medicine ground-truth. 21 Deep learning has been implemented to generate CTVIs from 4DCT with DIR-based CTVIs as the reference ground-truth. 22 Deep learning has also been successfully used to produce CTVIs from 4DCT with Technegas SPECT as the nuclear medicine ground-truth, which showed a higher degree of correlation compared with DIR-based CTVIs.…”
Section: Introductionmentioning
confidence: 99%
“…A recent systematic review has found that deep learning applied to functional lung imaging is a relatively small field with good opportunities for further research 20 . 4DCT perfusion images have been synthesized using a deep learning approach with MAA‐SPECT as the nuclear medicine ground‐truth 21 . Deep learning has been implemented to generate CTVIs from 4DCT with DIR‐based CTVIs as the reference ground‐truth 22 .…”
Section: Introductionmentioning
confidence: 99%